Infrastructure as Privilege - Wrisley, David Joseph (Historical reflections, 2023)
Exciting new modes of digital scholarship have emerged in recent years, providing us with expanded windows onto the past. This process has been accelerated by somewhat democratized ways of digitizing and analyzing source material. A main issue of contemporary knowledge production using digitized sources is how power can so easily be reinscribed into access to archives. The choice to digitize collections, even the existence of collections themselves, creates a great opportunity for research but also runs the risk of reinforcing the privilege and worldviews that have shaped and continue to shape the very processes of digitization and digitalization. Drawing on examples of Western and non-Western digital scholarship, this article argues that, although the digital facilitates greater public knowledge of collections, when it comes to decolonizing our research subjects, it also introduces significant layers of complexity. Keywords * decolonization, digital collections, digital humanities, digital scholarship, Global South, infrastructure, non-Western countries